A cross-sectional study to know the prevalence, pattern, and contributing factors associated with nomophobia in medical students - Dabhi, Hetal; Satodiya, Vimal; Garg, Suvidha; Goel, Ramita; Vala, Ashok (International Journal of Research in Medical Sciences, 2024)
Background: Now-a-days, Smartphone offers people great opportunities and luxuries. According to the Telecom Regulatory Authority of India (TRAI); in 2021, India had roughly 180.96 million mobile users, and issues by mobile phone use have been significantly increased in recent years Nomophobia is a modern phobia that appeared in this digital era. It is the conjunction of "nonmobile" and "phobia” and refers to the worry, anxiety, and discomfort associated with not having a mobile device when needed. The objectives of this study are to understand (a) prevalence of nomophobia in medical students; (b) association of Nomophobia with self-esteem among medical students; and (c) association of nomophobia with life satisfaction among medical students. Methods: This was an observational, cross-sectional, single-centred, self-assessable questionnaire-based study. 700 students (pursuing MBBS, internship or residency) from the government medical college, Bhavnagar were enrolled. The participants were assessed by proforma containing demographic details, a questionnaire of Nomophobia (NMPQ), Rosenberg Self-Esteem Scale (RSES), and Satisfaction with Life Scale (SWLS). The statistical analysis was done with Graph Pad Instat version 3.06 (San Diego, California, US). Proportions were compared by using the Chi-square test while NMPQ, RSES, and SWLS scores were compared by the Students t test. Results: We found all participants had some degree of nomophobia (29% mild, 31.29% moderate, and 5.43% severe). Nomophobia had a significant association with self-esteem and satisfaction with life. Conclusions: Participants with nomophobia are more likely to experience low self-esteem and poor satisfaction with life.